Lécba chronických uveitid dlouhodobou aplikací penicilínu - Stibor, V; Svoboda, J; Bartosová, L; Kondrová, J; Traurigová, I (Ceskoslovenska oftalmologie, 1992)
The authors followed up a group of 20 patients with chronic uveitis (10 men and 10 women), mean age 36.5 years. Despite treatment of the foci, they suffered on average from seven relapses of the disease, frequently several times in the course of one year. From the anamnestic aspect there was a significantly high number of spells of tonsillitis, respiratory infections and arthralgia. Half the cases of uveitis, mainly anterior, were bilateral. The patients suffered from dysimmunoglobulinaemia with low values of FW, ASLO, Latex. HLA B 27 was positive in five subjects. After one-year of Pendepon or Penclen administration (in half the patients with NORG) 18 patients did not develop a relapse for a period of 2-3 years. The method is simple, cheap, easy to use in field practice, in particular in junior patients. The clinical effect of treatment justifies the use of this method as an alternative of intermittent immunosuppression.
Keywords: časové faktory; Chronic Disease; Female; Adult; dospělí; Penicillins; peniciliny; Humans; ženské pohlaví; Time Factors; mužské pohlaví; Male; lidé; uveitida; lidé středního věku; Middle Aged; chronická nemoc; Uveitis